Perancangan Aplikasi Kriptografi Asimetris Dengan Menerapkan Metode Elliptic Curve Cryptography - Sari, Eka Indah (LPPM UNIKA Santo Thomas Medan, 2018)
Cryptography is one of the sciences used to maintain confidentiality and data security has been developing since ancient Greece. One cryptographic method that is quite reliable, stable and the parent of the popular cryptographic algorithms today is Elliptic Curve Cryptography (ECC). In this case the previous block encryption results are feedback into current block encryption. The trick, the current plaintext block is XORed first with the ciphertext block from the previous encryption, then the XOR results are entered into the encryption function. With ECC mode, each ciphertext block depends not only on the plaintext block but also on the all previous plaintext blocks, Implementation of the Elliptic Curve Cryptography (ECC) algorithm in this study was carried out by using an application built using visual basic programming language. Net 2008..